A Study on Teaching Mathematics Using Arts Integrated Learning: Warliart and Congruence of Triangles - Rao, N.BalajiBabu; Kumar, M Pavan; Hanchinalkar, Sujata B (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Art is the creative expression of an individual. This expression can be verbal, written, an enactment, or it can be visual, or any that has the potential or the ability to communicate human thoughts. Artistic expression in music, poetry, dance theatre, and forms has been an integral part of human growth and development. Since times immemorial, what has survived the fissures and ravages of time is only art. Art integrated learning is a cross-curricular approach to teaching and learning based on collaboration between the teaching of the subject with the teaching of Art (Visual/performing etc.), where Art, in any of its multiple forms, becomes the primary pathway to learning the subject/topic and also of assessment. The integration is meant not only to make the learning process (of the chosen subject area for integration) joyful, but it also lends itself to imbibing a greater appreciation and understanding of the art form being utilized for this purpose. In the present study, the researchers have tried to integrate art and mathematics by teaching the concept congruence of triangles using Warli art. It was observed that the students enjoyed learning the concept of congruence of triangles with the help of Warli art. The students were able to use different criteria such as Angle side angle (ASA), Side angle Side (SAS), side-side-side (SSS), and right-angle hypotenuse side (RHS) by using the Warli art form as a means. This not only made learning mathematics joyful and interesting but also brought out creative thinking among the students.